Implementation of the FastICA algorithm in sound source separation - Ghita, Cristian; Raicu, Razvan Doru; Pantelimon, Brandusa (2015 9th International Symposium on Advanced Topics in Electrical Engineering (ATEE), 2015)
The purpose of this paper is to analyze the use of the fixed-pointed algorithm FastICA on a mix of four voices with the aim of separating each of the voices. Two experiments where performed, one with real data with artificial mixing and the other one with real data with real mixing. Following these experiments, discussions were held and some conclusions were drawn.